Formulasi dan Uji Stabilitas Fisik Sediaan Gel Antiseptik Ekstrak Daun Sirih (Piper betle Linn.) dan Jeruk Nipis (Citrus aurantifolia Swingle) Menggunakan Gelling Agent Hydroxypropyl Methylcellulose (HPMC) - Bachtiar, Muhammad Rifky (Universitas Muhammadiyah Gresik, 2025)
In the era of the Covid-19 pandemic, hands are one of the main media for the spread of viruses or bacteria, so antiseptic preparations are needed as one of the preventive measures or prevention efforts. Many plants from natural ingredients that can be used to make antiseptics include betel leaf extract and lime juice. The selection of betel leaf and lime as ingredients for the manufacture of this hand sanitizer gel is due to the presence of flavonoids which have antioxidant and antibacterial functions. This study aims to determine the physical stability of hand antiseptic gel from betel leaf extract (Piper betle L.) and lime juice (Citrus aurantifolia Swingle) using HPMC base and to determine HPMC base at what concentration can produce antiseptic gel preparations. Betel leaf extract (Piper betle L.) and lime juice (Citrus aurantifolia Swingle) with good physical characteristics. This research is experimental using a qualitative descriptive method. The results of this study indicate that from the three formulas that have been made, the preparation is stable for 7 days and there is no change in smell, color, and shape. Based on the test results, it can be seen that the best formula is the HPMC concentration of 0.6 grams in terms of organoleptic, homogeneous, pH, adhesion and hedonism tests which also show the best with the highest total average value, which is equal to 3.3.